Plum-blossom needle in the treatment of insomnia in a patient with central retinal artery obstruction (梅花针治疗1例视网膜中央动脉阻塞患者失眠的护理体会) - CHEN Ping (陈平); HUANG Shaolan (黄少兰); YANG Jianying (杨剑英); ZHAO Junying (赵俊英); WANG Qiao (王俏); CHEN Yuanyuan (陈媛媛); LIANG Ying (梁颖); GUO Xiaoqin (郭晓勤) (中西医结合护理)
This article summarizes the effect of plum-blossom needle and nursing on relieving insomnia in a patient with central retinal artery occlusion. Based on Traditional Chinese Medicine syndrome differentiation, plum-blossom acupuncture therapy was conducted to relieve insomnia symptoms of the patient, and comprehensive nursing measures such as emotion regulation, diet nursing and health education effectively were carried out to improve the quality of life of the patient. (本文总结1例视网膜中央动脉阻塞(CRAO)后失眠患者采用梅花针治疗的护理经验。基于中医辨证施护原则, 结合梅花针治疗, 同时辅以情志护理、饮食护理及健康宣教等综合护理措施, 有效缓解了患者的失眠症状, 提升患者的生活质量。且该方法操作简便、安全可靠, 且无明显不良反应。)